A physiologically based pharmacokinetic model for chickens exposed to feed supplemented with monensin during their lifetime. Issue 4 (12th December 2016) - Henri, J.; Carrez, R.; Méda, B.; Laurentie, M.; Sanders, P.
Abstract : We developed a flow‐limited physiologically based pharmacokinetic model for residues of monensin in chickens and evaluated its predictive ability by comparing it with an external data set describing concentration decays after the end of treatment. One advantage of this model is that the values for most parameters (34 of 38) were taken directly from the literature or from field data (for growth and feed intake). Our model included growth (changes in body weight) to describe exposure throughout the life of the chicken. We carried out a local sensitivity analysis to evaluate the relative importance of model parameters on model outputs and revealed the predominant influence of 19 parameters (including three estimated ones): seven pharmacokinetic parameters, five physiological parameters and seven animal performance parameters. Our model estimated the relative bioavailability of monensin as feed additive at 3.9%, which is even lower than the absolute bioavailability in solution (29.91%). Our model can be used for extrapolations of farming conditions, such as monensin supplementation or building lighting programme (which may have a significant impact for short half‐life molecules such as monensin). This validated PBPK model may also be useful for interspecies extrapolations or withdrawal period calculations for modified dosage regimens.